Alterations of Gut Mycobiota Profiles in Adenoma and Colorectal Cancer - Gao, Renyuan; Xia, Kai; Wu, Minkang; Zhong, Hui; Sun, Jing; Zhu, Yin; Huang, Linsheng; Wu, Xiaocai; Yin, Lu; Yang, Rong; Chen, Chunqiu; Qin, Huanlong (Frontiers in Cellular and Infection Microbiology, 2022)
Accumulative evidence supported gut microbiota dysbiosis contributed to colorectal cancer and adenoma. However, less study revealed the altered gut mycobiota architectures in colorectal cancer. The present study characterized the gut mycobiota profiles in colorectal cancer patients by metagenomic sequencing. Malassezia restricta increased while Leucoagaricus_sp_SymCcos and fungal_sp_ARF18 significantly decreased in adenoma. Phanerochaete_chrysosporium, Lachancea_waltii and Aspergillus_rambellii were the top three fungi that significantly enriched in colorectal cancer while Candida_versatilis, Pseudocercospora_pini_densiflorae and Candida_sp_JCM_15000 were dominant in the healthy controls. Thirteen fungi, ranked as critical biomarkers in diagnosing colorectal cancer, showed positive associations among all samples. Lachancea_waltii and Phanerochaete_chrysosporium showed the most significant association within CRC. The values of area under the operative characteristics curve (AUROC) of selected 13 mycobiota were 0.926 in the training model and 0.757 in the ten-fold validation model. Our study provided a reliable investigation of the alterations of gut mycobiota in the development of colorectal cancer and established a convinced diagnostic model for colorectal cancer, which might improve the treatment strategy for colorectal cancer in the future.